The protective effect of grit on clinical nurses’ occupational psychological distress: Mediating and suppressing effects of Hope - Peng, Xueping; Wu, Dongmei (Frontiers in Psychology, 2022)
As at a high-risk group of psychological distress, nurses generally experience varying degrees of stress, anxiety, and depression. This paper identifies the positive factors that can negatively regulate the psychological pain of clinical nurses and their mechanisms of action, providing reliable references for clinical nurse support management. This study observed the effects and mechanism of Hope and the Two components of Grit (Consistency of Interest and Perseverance of Effort) on clinical nurses' psychological distress (Depression, Anxiety, and Stress). A total of 635 Chinese clinical nurses (90.4% female) completed an anonymous questionnaire for the study. As expected, Hope, Consistency of Interest (CI), and Perseverance of Effort (PE) were negatively correlated with the three indicators of psychological distress (r = 0.18-0.54, p < 0.05). Path analysis results showed that Hope significantly mediated the negative effect of CI on psychological distress, with an effect of 12.96%。 Hope also covered up the PE on psychological distress, the effect of 110.63%. The results showed that Hope significantly mediates the effect of CI and PE on psychological distress. Based on these results, it can conclude that Grit and Hope have a protective effect on psychological distress. Significantly increasing the level of Hope or Grit is an effective way to prevent and reduce psychological distress in clinical nurses.